2013
DOI: 10.1117/1.jrs.7.073578
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing-based determination of understory grass greening stage over boreal forest

Abstract: Downloaded From: http://remotesensing.spiedigitallibrary.org/ on 06/23/2016 Terms of Use: http://spiedigitallibrary.org/ss/TermsOfUse.aspxAbstract. Our objective was the determination of understory grass greening stage (GGS: defined as the date when 75% of the grass in the surrounding area of a particular location would be green) using remote sensing data over the boreal-dominant forested regions in the Canadian province of Alberta. We used moderate resolution imaging spectroradiometer (MODIS)-derived accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…At the end of the peak of the growing season, all six natural subregions experienced much less lightning-caused fires, which could be related to both the understory and overstory being fully developed by the peak of the growing season, thereby reducing fuel flammability [44]. In addition, the weather-in particular temperature regimes-plays an important role in influencing the vegetation phenology [22][23][24]. For example, we observed that temperatures start to increase in the spring, and this trend continues until it reaches a peak during the growing season (see Figure 6 as an example).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the end of the peak of the growing season, all six natural subregions experienced much less lightning-caused fires, which could be related to both the understory and overstory being fully developed by the peak of the growing season, thereby reducing fuel flammability [44]. In addition, the weather-in particular temperature regimes-plays an important role in influencing the vegetation phenology [22][23][24]. For example, we observed that temperatures start to increase in the spring, and this trend continues until it reaches a peak during the growing season (see Figure 6 as an example).…”
Section: Discussionmentioning
confidence: 99%
“…Between these two indices, the NDWI has been widely used in fire-related studies, such as forest fire vulnerability mapping [14], fire danger condition [10], fire risk prediction [15,16], fire behavior prediction [17], post-fire evaluation and vegetation response [18,19], and the beginning of the fire season [20,21]. In addition, it has been applied to the study of vegetation growth stages, such as coniferous needle flushing [22], understory grass green stage [23], and deciduous leaf out [24], which might be associated with fire occurrences. Other studies have employed NDVI to study/model fire occurrences [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…To define cold days/spells, one of the simplified methods is to use a single threshold of a specific air temperature corresponding to the daily maximum (T max ), minimum (T min ), or average (T avg ) temperature [6,18,19]. Using such a single threshold of temperature for a country creates some issues, which are not appropriate for the following instances: (i) large waterbodies being present in some parts of a country [20], as areas adjacent to waterbodies usually have mild temperature; (ii) countries spanning over a larger range of latitudes [21,22], as higher latitudes predominate relatively cooler temperatures [23,24]; and (iii) diverse topography, which produces temperature variations, even in cases of narrow latitude [25]. In Bangladesh, a single T min threshold of ≤10 • C is used for the whole country to define a cold day, and a cold spell is declared when at least two nearby weather stations show three and more consecutive cold days [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…In another study by Hu et al [9] used both 8-day and 16-day composites of MODIS-based Ts over the period of January 2011 to June 2018 for agricultural drought monitoring in the Hetao Plain in Inner Mongolia of Northwest China. Some other studies also used remote sensing based Ts in determining several biophysical parameters of vegetation, such as deciduous phenology [10], understory grass greening stage [11], and surface wetness conditions and growing degree days [12].…”
Section: Introductionmentioning
confidence: 99%